War and time in Semejante a la noche, of Alejo Carpentier (2009)
In the Light of the importance that Arendt, Ricoeur y Nussbaum grants to literature in order to analyze characteristic problems of human condition, in this essay is studied how and why in "Semejante a la noche", a short story written by Alejo Carpentier,